Selection of progenitors for increase in oil content in soybean - Josiane Isabela da Silva Rodrigues (Revista Ceres)
ABSTRACT The low genetic diversity brings limitation to breeding, because genetically similar genotypes share alleles in common, causing little complementarity and low vigor due to the low levels of heterozygosity in crosses. The objective of this work was to analyze the oil content and genetic diversity of soybean genotypes (Glycine max (L.) Merrill) based on QTL regions of this trait for choice of progenitors for increase in oil content. Twenty-two genotypes with wide variation in oil content, including cultivars with high oil contents, were cultivated in different Brazilian conditions and the oil content of the grains was quantified by infrared spectrometry. Microsatellite markers selected based on QTL regions for oil content in soybean were analyzed to estimate the genetic diversity. In these studies, a wide variation in oil content (17.28-23.01%) and a reasonable diversity among the genotypes were observed, being PI181544 the most divergent genotype, followed by Suprema. The genotypes PI371610/Suprema and Suprema/CD01RR8384 showed genetic distance and higher oil contents in the grains, while the cultivars Suprema and CD01RR8384 had the highest oil contents and proved to be little genetically related. These genotypes are promising progenitors for selection of high oil content in soybean.